2022
DOI: 10.1108/ajems-03-2022-0105
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Saharan Africa's rising public debt stock: before another debt relief!

Abstract: PurposeIn light of the recent calls for another round of debt relief for African countries, by African finance ministers and governments, the aim of the study is twofold. First, the study examined the effect of public debt on macroeconomic performance. Two, the study also examined whether previous debt relief has impacted positively on sub-Saharan African economies.Design/methodology/approachThe study adopts the two-step system GMM that accounts for potential endogeneity and feedback effect in dynamic panel mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In particular, the total external debt stock in the public debt portfolio increased dramatically from $465 billion in 2015 to about $702 billion in 2020 (IDS, 2021). Other scholars (see Olaoye, 2022a,b; Owusu‐Nantwi & Erickson, 2016) have also found that public debt can be a significant driver of economic growth in SSA.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In particular, the total external debt stock in the public debt portfolio increased dramatically from $465 billion in 2015 to about $702 billion in 2020 (IDS, 2021). Other scholars (see Olaoye, 2022a,b; Owusu‐Nantwi & Erickson, 2016) have also found that public debt can be a significant driver of economic growth in SSA.…”
Section: Introductionmentioning
confidence: 98%
“…The available evidence shows that a large number of African countries experienced strong economic growth in the last few decades, especially, in the last 10–15 years (Mijiyawa, 2013). However, some scholars (Avramovic, 1991; Olaoye, 2022a,b; The African Capacity Building Foundation, 2017; Whajah et al, 2019) have suggested that Africa's growth may not be unconnected with the recent and rapid increase in public borrowing across sub‐Saharan African countries (hereafter, SSA). Many African countries, following the COVID‐19 pandemic, have embarked on a new wave of borrowing to scale up public investment and spur economic growth (Olaoye & Olomola, 2022; Sennoga & Balma, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the study indicate that declining exports negatively affect output growth and deteriorates external debt dynamics to unsustainability in the long‐run. Olaoye (2023) investigates external debt sustainability, employing GMM and two‐stage‐least‐square (2sls) models, in African economies and the findings indicate that the debt reliefs provided to African economies proved instrumental only temporarily. The findings show that corruption and inefficiency in public debt allocations have adverse effects on fiscal deficits and the output growth of African economies.…”
Section: Introductionmentioning
confidence: 99%
“…One major issue that is attracting the attention of scholars and policymakers globally, and in sub‐Saharan African (SSA) countries, in particular, is the rapid increase in the level of public debts over the last few decades (Akram, 2016; Beqiraj et al, 2018; Carner et al, 2021; Fambeu et al, 2022; Kassouri et al, 2021; Law et al, 2021; Makun, 2021; Napo, 2022; Olaoye, 2022a, 2022b; Owusu‐Nantwi & Erickson, 2016; Sennoga & Balma, 2022; Wang et al, 2021). In the last two decades, the total public debt for SSA increased from an average of 27% of gross domestic product (GDP) in 2010 to over 56% in 2018.…”
Section: Introductionmentioning
confidence: 99%